Association between motor skills and executive function of children with autism spectrum disorder in Taiwan and the United States - Sung, Ming-Chih; McClelland, Megan M.; Massey, William; Logan, Samuel W.; MacDonald, Megan (Frontiers in Public Health, 2024)
Objective The purpose of this study was to examine the relationship between parent ratings of motor skills and executive function (EF) in children with autism spectrum disorder (ASD) in the United States and Taiwan. Materials and method One hundred and seventy-two parents/legal guardians of children (4–6 years and 11 months old) with ASD were recruited from two countries, Taiwan (n = 100) and the United States (n = 72). The parents or guardians of the child with ASD completed a questionnaire including demographic information, child’s motor skills (using Children Activity Scale – Parents, ChAS-P), and child’s EF (using Childhood Executive Functioning Inventory, CHEXI). A series of hierarchical multiple regressions were conducted to determine whether ChAS-P (total motor score, fine motor skills, and gross motor skill) was associated with CHEXI (total EF score, working memory, and inhibition), after controlling for covariates (i.e., age, gender, race, body mass index, whether children received physical activity or cognitive training, parental education level). Results Total motor skills, fine motor skills, and gross motor skills were significantly associated with EF in both working memory and inhibition as rated by parents in both countries (β = 0.21–0.57, p < 0.01), with the exception of a non-significant association between parent-rated total motor skills, fine motor skills, and gross motor skills, and inhibition among Taiwanese children with ASD. In addition, the associations between parent ratings of motor skills (i.e., fine motor and gross motor skills) and EF (i.e., working memory and inhibition) were similar between the two countries. Conclusion Positive associations with specific aspects of parent ratings of fine motor and gross motor skills and working memory and inhibition were found in children with ASD from both countries. These findings have implications for future interventions and programs focused on improving early motor skills and EF development for young children with ASD from Taiwan and the United States.